The quest for throughput legitimacy: the EEAS, EU delegations and the contested structures of European diplomacy - Maurer, H; Morgenstern-Pomorski, J-H (Taylor and Francis, 2018)
The European External Action Service (EEAS) and its EU delegations have developed the notion of “being of service to EU member states” in EU foreign policy making as their unique selling point for the past eight years. In this paper, we discuss how the EEAS and its delegation network sought to establish throughput legitimacy and why being considered legitimate is a particular concern for them. We trace the conflicting expectations of “roles” expressed during the Convention on the Future of Europe and the Lisbon Treaty and show how the EEAS and EU delegations responded to treaty implementation. Because the EEAS and EU delegations were treated as separate parts during the discussions of the time, we are able to compare how different levels of role contestation lead to different strategies for legitimacy construction in practice.